Nanoparticle magnetic film and electronic component

By using nanoparticle magnetic films of Fe and Co elements in the inductor, combined with the second phase of O, N or F, to form a nanoparticle structure with high resistivity and permeability, the problem of insufficient permeability and miniaturization of inductors under high frequency driving in the prior art is solved, and high frequency driving and miniaturization of power circuits are realized.

CN119742148APending Publication Date: 2025-04-01TDK CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411355508.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-31
Filing Date
2024-09-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to develop nanoparticle magnetic films with high resistivity relative to saturated magnetic flux density Bs, which limits the permeability and miniaturization of the inductor under high frequency drive.

Method used

A magnetic film having a nanoparticle structure with a tiny region of the first phase dispersed in the second phase, wherein the first phase contains Fe and Co, and the second phase contains elements such as O, N, or F. The nanoparticle magnetic film is formed on the substrate by sputtering method, and the rotation speed and process parameters of the rotating plate are adjusted, and the atomic ratio of Fe/(Fe+Co) and the volume ratio of the magnetic film are controlled to improve the resistivity and magnetic permeability.

Benefits of technology

It realizes a nanoparticle magnetic film with high magnetic permeability and resistivity under high frequency drive, which is suitable for miniaturized inductors and circuit substrates, and improves the high-frequency driving capability of power supply circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742148A_ABST
    Figure CN119742148A_ABST
Patent Text Reader

Abstract

The invention relates to a nanoparticle magnetic film and an electronic component. The nanoparticle magnetic film has a structure in which minute regions of the first phase are dispersed in the second phase. The first phase contains Fe and Co, and the second phase contains one or more elements selected from the group consisting of O, N, and F. A measurement range is set for the nanoparticle magnetic film, the measurement range is divided into 80000 or more grids of 1 nm * 1 nm * 1 nm, and Fe / (Fe + Co) for each grid is measured at an atomic ratio, and in this case, the CV value of Fe / (Fe + Co) calculated for each grid is 0.150-0.500 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nano-particle magnetic film and an electronic component. Background Art

[0002] In recent years, in mobile devices such as smartphones and smart watches, there are simultaneous requirements for larger display screens, increased battery capacity, smaller size, and lighter weight. The requirements for larger display screens and increased battery capacity are opposite to the requirements for smaller size and lighter weight. In order to achieve these opposite requirements, it is required to miniaturize the circuit substrate. In the circuit substrate, it is also particularly required to miniaturize the power supply circuit that occupies a larger area. Moreover, in the power supply circuit, it is also particularly required to miniaturize the inductor that has a large mounting area.

[0003] In order to reduce the size of the inductor, it is particularly effective to increase the driving frequency of the power supply circuit. In order to increase the driving frequency of the power supply circuit, a switching element that can be driven at a high frequency is required.

[0004] Traditionally, the switching elements used in power circuits are made of silicon, so the driving frequency of the power circuit is limited. This is a problem caused by the limit of the physical properties of silicon. However, in recent years, semiconductors such as GaN and SiC, which have better physical properties than silicon, are being used for switching elements.

[0005] By using semiconductors with good high-frequency characteristics such as GaN for switching elements, high-frequency driving of switching elements can be achieved, and high-frequency driving of power supply circuits can be realized. For example, compared with previous silicon switching elements, switching elements made of GaN can switch at a very high frequency, and can drive power supply circuits at a very high frequency.

[0006] By driving the power circuit at high frequency, passive components, especially large-sized power inductors, can be greatly miniaturized. Therefore, the power circuit can be greatly miniaturized. In order to drive the power inductor at high frequency, it is necessary to realize a magnetic body with high magnetic permeability in the high frequency region and use it as the core material of the inductor.

[0007] Thin film inductors are the most suitable form of small inductors for power supplies that can handle high-frequency drives. Thin film inductors are manufactured by laminating coils, terminals, magnetic films, and insulating layers on a substrate through a semiconductor process. In thin film inductors, the magnetic film becomes the magnetic core, so the characteristics of thin film inductors are highly dependent on the characteristics of the magnetic film.

[0008] Patent Document 1 describes an amorphous alloy having a structure in which fine particles containing a metal element are dispersed in an amorphous film composed of a nitrogen compound. Such a structure is sometimes referred to as a nanoparticle structure. Furthermore, a magnetic film having such a structure is sometimes referred to as a nanoparticle magnetic film.

[0009] Nanogranular magnetic films have a higher saturation flux density Bs than ferrite materials and a higher resistivity ρ than general magnetic alloys, and therefore have high magnetic permeability under high-frequency driving. Therefore, the application of nanogranular magnetic films in thin film inductors has been studied.

[0010] Patent Document 2 describes a nanogranular magnetic film containing elements such as Fe and Co, and having various parameters that can be measured by a three-dimensional atom probe within a specific range. The nanogranular magnetic film has a high coercive force and a low saturation magnetic flux density.

[0011] Prior art literature

[0012] Patent Literature

[0013] Patent Document 1: Japanese Patent Application Laid-Open No. 60-152651

[0014] Patent Document 2: International Publication No. 2023 / 127199 Summary of the invention

[0015] Technical problem to be solved by the invention

[0016] An object of the present invention is to provide a nanogranular magnetic film having a high resistivity relative to the saturation magnetic flux density Bs.

[0017] Technical solutions for solving technical problems

[0018] In order to achieve the above object, the nanogranular magnetic film involved in the present invention is a nanogranular magnetic film having a structure in which micro-regions of a first phase are dispersed in a second phase, wherein:

[0019] The first phase contains Fe and Co, and the second phase contains one or more selected from O, N and F.

[0020] A measurement range is set for the nanogranular magnetic film, the measurement range is divided into 80,000 or more 1 nm×1 nm×1 nm grids, and Fe / (Fe+Co) of each grid is measured as an atomic ratio. In this case,

[0021] The CV value of Fe / (Fe+Co) calculated for each mesh is 0.150 or more and 0.500 or less.

[0022] The volume ratio of the first phase to the total volume of the first phase and the second phase may be 40% to 65%.

[0023] The average value of Fe / (Fe+Co) calculated for each mesh may be 0.15 or more and 0.85 or less.

[0024] The electronic component according to the present invention includes the above-mentioned nanogranular magnetic film. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a schematic cross-sectional view of a nanogranular magnetic film.

[0026] Figure 2 It is a schematic diagram showing a cross section of a production apparatus.

[0027] Figure 3 is a schematic diagram of the manufacturing apparatus.

[0028] Figure 4 is a schematic diagram of the manufacturing apparatus.

[0029] Explanation of symbols:

[0030] 1…Nanogranular magnetic films

[0031] 11…Phase 1

[0032] 12…Phase 2

[0033] 111…Rotating parts

[0034] 111a…Rotating plate

[0035] 111b…Rotation axis

[0036] 113…Substrate

[0037] 121…Sputtering device

[0038] 123…Sputtering targets

[0039] 131…Baffle DETAILED DESCRIPTION

[0040] Hereinafter, embodiments of the present invention will be described with reference to the drawings.

[0041] like Figure 1 As shown, the nanogranular magnetic film 1 of the present embodiment has a structure in which minute regions of the first phase 11 are dispersed in the second phase 12 , that is, a nanogranular structure.

[0042] The nanogranular magnetic film is a thin film having the above structure and in which the second phase is not a resin. Even if a ribbon or a molded body literally has a structure in which minute regions of the first phase 11 are dispersed in the second phase 12, it is not a nanogranular magnetic film.

[0043] The average size of the micro-region of the first phase 11 is nanometer size, that is, 30 nm or less. The average size of the micro-region of the first phase 11 may also be 15 nm or less. There is no particular limitation on the method for measuring the size of the micro-region of the first phase 11. For example, the equivalent circle diameter of the micro-region of the first phase 11 on the cross section of the nanogranular magnetic film 1 may also be used as the size of the micro-region of the first phase 11.

[0044] Furthermore, the equivalent circle diameter of the micro region of the first phase 11 on the cross section of the nanogranular magnetic film 1 is the diameter of a circle having an area equal to the area of ​​the micro region of the first phase 11 on the cross section of the nanogranular magnetic film 1 .

[0045] The first phase 11 is a phase containing metal elements. Specifically, it contains Fe and Co. There is no particular limitation on how Fe and Co are contained in the first phase 11. For example, Fe and Co may be contained in the first phase 11 in any proportion, Fe and Co may be contained in the first phase 11 as alloys with other metal elements, or Fe and Co may be contained in the first phase 11 as compounds with other elements. The compound contained in the first phase 11 may also be an oxide magnetic body. For example, it may be ferrite.

[0046] The total content of Fe and Co in the first phase 11 is not particularly limited. The ratio of the total content of Fe and Co in the first phase 11 to the total content of Fe, Co, X1, and X2 may be 75 at% or more, 80 at% or more, 90 at% or more, or 95 at% or more. However, when calculating the ratio, the element whose content ratio in the second phase 12 is higher than that in the first phase 11 is not included in X1 and X2.

[0047] X1 is a metalloid element, for example, one or more metalloid elements selected from B, Si, P, C and Ge.

[0048] X2 is a metal element other than Fe and Co. For example, it may be one or more metal elements selected from Nb, Mo, Cu, Ti, Zr, Cr, Mn, V, W, Al, and Ni.

[0049] The first phase 11 may contain elements other than Fe, Co, X1 and X2. The total content of elements other than Fe, Co, X1 and X2 may be 10 at% or less, or 5 at% or less relative to the total content of Fe, Co, X1 and X2.

[0050] The second phase 12 is a phase containing non-metallic elements. Specifically, the second phase 12 is a phase containing one or more elements selected from O, N and F. There is no particular limitation on how one or more elements selected from O, N and F are included in the second phase 12. For example, one or more elements selected from O, N and F may also be included in the second phase 12 as compounds with other elements. That is, the second phase 12 may also contain oxides, nitrides, oxynitrides and / or fluorides of some elements other than O, N and F. The second phase 12 may also contain oxides, nitrides and / or fluorides of some elements other than O, N and F. In addition, the second phase 12 may also be a mixed phase of oxides, nitrides and / or fluorides.

[0051] The type of compound contained in the second phase 12 is not particularly limited. For example, SiO2, Al2O3, AlN, Si3N4, MgF2, BN, MgO, GaO2, GeO2, Si3N4·Al2O3, etc. can be cited. In addition, the oxides in the above compounds may be oxynitrides in which oxygen is partially replaced by nitrogen. That is, the compound contained in the second phase 12 may be oxynitrides of Si, oxynitrides of Al, oxynitrides of Mg, oxynitrides of Ga, oxynitrides of Ge, or oxynitrides of Si and oxynitrides of Al.

[0052] When the compound contained in the second phase 12 is a nitrogen oxide, the ratio of the nitrogen content in the second phase 12 to the total content of oxygen and nitrogen (hereinafter, sometimes recorded as N / (N+O)) can be greater than 0at% and less than 46at%, or can be greater than 15at% and less than 46at%. There is no particular limitation on the method for determining N / (N+O) in the second phase 12. For example, it can also be determined using a pulse heating melting extraction method. However, it is difficult to use XRF. This is because it is difficult to measure the content of elements with small atomic numbers such as O and N, and it is difficult to ensure accuracy.

[0053] Alternatively, the nanogranular magnetic film of this embodiment may be composed of (Fe x Co y X1 a X2 b )-X3 composition,

[0054] X1 is one or more selected from B, P, C and Ge,

[0055] X2 is one or more selected from Nb, Mo, Cu, Al, Ti, Zr, Cr, Mn, V, W, Al, and Ni,

[0056] X3 is one or more selected from SiO2, Al2O3, AlN, ZnO, MgF2, GeO2, Si oxynitride, Al oxynitride, Zn oxynitride, Ge oxynitride, and satisfies:

[0057] 0.15≤x≤0.85

[0058] 0.15≤y≤0.85

[0059] 0≤a≤5.0

[0060] 0≤b≤10.0

[0061] 0.90≤x+y+a+b≤1.00.

[0062] The above formula indicates that the composition of the first phase 11 is Fe in terms of atomic ratio. x Co y X1 a X2 b , the second phase 12 is composed of X3. X3 may also be one or more selected from SiO2, Al2O3, AlN, ZnO, MgF2, GeO2, and Si nitride oxide (recorded as Si-ON). The volume ratio of the first phase 11 and the second phase 12 will be described in detail later.

[0063] The nanogranular magnetic film 1 of the present embodiment may contain, as impurities, elements that are not contained in the elements constituting the first phase 11 and are not contained in the elements constituting the second phase 12. When the total ratio of the elements (excluding O, N and F) contained in the nanogranular magnetic film is 100 at%, the impurities may be contained in an amount of 5 at% or less.

[0064] There is no particular limitation on the volume ratio of the first phase 11 to the total volume of the first phase 11 and the second phase 12. For example, it may be 70% or less, or 65% or less. That is, when the volume ratio of the first phase 11 is V1 and the volume ratio of the second phase 12 is V2, V1 / (V1+V2) may be 0.70 or less (70% or less), and V1 / (V1+V2) may be 0.65 or less (65% or less). V1 / (V1+V2) may be 0.60 or less (60% or less). The larger the volume ratio of the first phase 11 to the total volume of the first phase 11 and the second phase 12, the higher the Bs, but the lower the resistivity.

[0065] There is no lower limit in particular for the volume ratio of the first phase 11 to the total volume of the first phase 11 and the second phase 12. It can be 30% or more, or 35% or more. That is, V1 / (V1+V2) can be 0.30 or more (30% or more), or 0.35 or more (35% or more). V1 / (V1+V2) can also be 0.40 or more (40% or more). The smaller the volume ratio of the first phase 11 to the total volume of the first phase 11 and the second phase 12, the higher the resistivity, but the lower the Bs.

[0066] The first phase 11 may also have a crystal structure. Specifically, the first phase 11 may also have a bcc crystal structure. By having a bcc crystal structure, the saturation magnetic flux density Bs is likely to be higher. The average grain size of the crystal contained in the crystal structure of the first phase may be greater than 1 nm and less than 30 nm, and more preferably may be greater than 1.5 nm and less than 15 nm.

[0067] The confirmation method of the average crystal grain size of the above-mentioned crystal structure and crystallization is not particularly limited. For example, the crystal structure can be confirmed by the analysis of the X-ray diffraction pattern utilizing XRD, the analysis of the electron diffraction pattern utilizing TEM etc. In addition, the average crystal grain size can be confirmed by TEM image, STEM image etc. In addition, the average size of the micro-region of the above-mentioned first phase 11 can be regarded as the average crystal grain size of crystallization.

[0068] There is no particular limitation on the method for measuring the volume ratio V1 / (V1+V2) of the first phase 11 relative to the total volume of the first phase 11 and the second phase 12. For example, it can be calculated based on the measurement results of XRF of the nanogranular magnetic film 1. Alternatively, it is also possible to observe the cross section of the nanogranular magnetic film 1 using TEM and calculate based on the area of ​​the first phase 11 relative to the total area of ​​the first phase 11 and the second phase 12. In this case, the area ratio is converted into a volume ratio.

[0069] The nanogranular magnetic film 1 may include only the first phase 11 and the second phase 12, but may also include a different phase other than the first phase 11 and the second phase 12. The ratio of the different phase is not particularly limited, but when a cross section of the nanogranular magnetic film 1 is observed using a TEM, the area ratio of the different phase may be 10% or less. In addition, a part or all of the different phase may be voids.

[0070] exist Figure 1 In the embodiment, all the first phases 11 exist separately from each other, but some of the first phases 11 may be connected to each other.

[0071] The thickness of the nanogranular magnetic film 1 is arbitrary. For example, it can be set to be greater than 50nm and less than 200000nm. In addition, a suitable thickness can be appropriately selected according to the application. The method for measuring the thickness of the nanogranular magnetic film 1 is not particularly limited. For example, it can be measured using TEM, SEM, height difference film thickness meter, etc. In addition, the reliability of the obtained measurement results can be confirmed by obtaining correlation between multiple measurement devices in advance.

[0072] The volume of the nanoparticle magnetic film 1 is set to 80000nm 3 The above measurement range is divided into more than 80,000 1nm×1nm×1nm cube grids, and the atomic ratio of the constituent elements is measured for all grids. Then, Fe / (Fe+Co) is calculated in each grid and its CV value is calculated. The CV value is a parameter calculated by dividing the standard deviation by the average value.

[0073] The above-mentioned measurement can be performed by a three-dimensional atom probe (3DAP).

[0074] The CV value of Fe / (Fe+Co) in this embodiment is 0.150 or more and 0.500 or less. Compared with a conventional nanogranular magnetic film having the same composition and structure except that the CV value of Fe / (Fe+Co) is outside the above range, the resistivity of the nanogranular magnetic film with the CV value of Fe / (Fe+Co) within the above range relative to Bs becomes higher. That is, it becomes a more excellent material as a core material of a thin film inductor.

[0075] The average value of Fe / (Fe+Co) calculated for each mesh may be 0.15 or more and 0.85 or less. The average value of Fe / (Fe+Co) calculated for each mesh is substantially consistent with the average value of Fe / (Fe+Co) of the entire nanogranular magnetic film.

[0076] Next, a method for producing the nanogranular magnetic film according to the present embodiment will be described.

[0077] The nanogranular magnetic film of this embodiment is formed by using, for example, Figure 2 to Figure 4 The manufacturing apparatus shown is used for the sputtering method. Figure 2 It is a schematic diagram showing a cross section of a production apparatus. Figure 3 It is along Figure 2 Schematic diagram of the manufacturing device (especially the rotating plate 111a and the substrate 113) observed in the direction of the arrow on the III-III line. Figure 4 It is along Figure 2 Schematic diagram of the manufacturing device (especially the baffle 131 and the sputtering target 123) observed in the direction of the arrows on line IV-IV.

[0078] The substrate 113 on which the nanogranular magnetic film is sputtered is fixed to the rotating plate 111a of the rotating member 111. The rotating plate 111a is fixed to the rotating shaft 111b.

[0079] The type of substrate used as the substrate 113 for sputtering the nanoparticle magnetic film is arbitrary. For example, a silicon substrate, a silicon substrate with a thermal oxide film, an MgO substrate, a (non-magnetic) ferrite substrate, a sapphire substrate, a glass substrate, a glass epoxy substrate, etc. can be cited. However, the type of substrate is not limited to these, and various ceramic substrates or various semiconductor substrates can be used.

[0080] Components (such as coils and wiring) constituting products or parts (such as thin film inductors) may also be fabricated on the above-mentioned various substrates. For example, coil patterns or wiring patterns for thin film inductors may also be fabricated on substrates for thin film inductors.

[0081] In addition, a foil or sheet of metal, plastic, resin, or the like may be used as the substrate 113 instead of the above-mentioned various substrates.

[0082] As a pre-treatment of the substrate 113, it is preferred to perform surface treatment under normal pressure by the UV / O3 method and surface treatment in vacuum such as reverse sputtering or ion milling, plasma cleaning, etc. The film thickness of the magnetic film used for the thin film inductor becomes thicker, so the problem of film peeling caused by stress is large. However, by performing both of the above-mentioned surface treatments, the problem of film peeling is greatly improved. The processing time of each surface treatment is not particularly limited. For example, the processing time of the UV / O3 method can also be set to more than 0.5 minutes and less than 60 minutes. In addition, the processing time of reverse sputtering when reverse sputtering is performed as a surface treatment in a vacuum can also be set to more than 0.1 minutes and less than 20 minutes.

[0083] Figure 3 , Figure 4 The shapes of the rotating plate 111a and the baffle 131 are not particularly limited. For example, the outer circumference may also be a perfect circle. Figure 2 The intersection of the imaginary line C and the surface of the rotating plate 111a having the substrate 113 is set as point C'. Figure 2 The intersection of the imaginary line C and the baffle 131 is set as point C". Point C' is the center of the rotating plate 111a whose outer circumference is a perfect circle, and point C" is the center of the baffle 131 whose outer circumference is a perfect circle.

[0084] The sputtering target 123 is mounted on the sputtering device 121. The type of the sputtering target 123 is arbitrary. However, in order to easily obtain the nanogranular magnetic film having the CV value of Fe / (Fe+Co) of 0.150 or more and 0.500 or less, it is preferable to use a sputtering target 123 made by mixing and sintering Fe and Co, or an FeCo alloy and a compound mainly contained in the second phase.

[0085] In addition, a chip composed of a monomer or compound of an element other than Fe, Co, and the compound mainly contained in the second phase may be appropriately disposed on the surface of the sputtering target 123. By disposing the chip, a monomer or compound of an element other than Fe, Co, and the element contained in the compound mainly contained in the second phase can be included in the nanogranular magnetic film. In addition, when a monomer or compound of an element other than Fe, Co, and the element contained in the compound mainly contained in the second phase is included in the nanogranular magnetic film by the above method, it may be included in the first phase or in the second phase.

[0086] However, when a target material in which Fe chips, Co chips, and / or chips of a compound mainly contained in the second phase are arranged on the surface of a target material produced by a sintering method or a melting method is used as a sputtering target material 123, instead of using the above-mentioned mixed sintered sputtering target material as the sputtering target material 123, the CV value of Fe / (Fe+Co) is easily reduced, and the resistivity relative to Bs is reduced. In addition, as the above-mentioned target material produced by a sintering method or a melting method, a target material composed only of an FeCo alloy or a target material composed only of a compound mainly contained in the second phase can be cited.

[0087] The type of the sputtering device 121 is not particularly limited as long as it can form a nanogranular magnetic film on the substrate 113 by sputtering.

[0088] like Figure 4 As shown, the baffle 131 has holes above the sputtering target 123 .

[0089] Then, the rotating shaft 111 b is rotated to perform sputtering while rotating the rotating plate 111 a , thereby forming a nanogranular magnetic film intermittently on the substrate 113 .

[0090] By appropriately adjusting the rotation speed of the rotating plate 111a or the lengths of L1 to L5, the continuous film forming time or the continuous film forming thickness of the nanogranular magnetic film is changed. Then, a multilayer film of the nanogranular magnetic film is pseudo-formed. That is, by repeating the film forming step and the relaxation step, a multilayer film of the nanogranular magnetic film is pseudo-formed.

[0091] In fact, even with the use of TEM or the like, it is not possible to confirm where the boundaries between the films are located, so it is recorded as "suspectedly". However, by suspiciously forming a multilayer film of the nanogranular magnetic film, a nanogranular magnetic film having a CV value of Fe / (Fe+Co) of 0.150 or more and 0.500 or less, particularly 0.150 or more is formed. Moreover, the resistivity of the formed nanogranular magnetic film relative to Bs increases. The reason for this is not clear, but it is believed that the stress in the nanogranular magnetic film is relaxed by intermittently forming the nanogranular magnetic film.

[0092] The film forming time of each layer of the multilayer film formed in a suspected manner (hereinafter, sometimes described as the continuous film forming time) and the film forming thickness of each layer (hereinafter, sometimes described as the continuous film forming thickness) are not particularly limited. The continuous film forming time may also be 0.7 seconds to 5.0 seconds, in particular, 3.4 seconds or less. The continuous film forming thickness may also be 0.4 nm to 3.0 nm, in particular, 2.0 nm or less. In particular, when the continuous film forming time and the continuous film forming thickness are increased by reducing the rotation speed, there is a tendency that the CV value of Fe / (Fe+Co) is easily reduced, and the resistivity relative to Bs becomes smaller.

[0093] The atmosphere during sputtering is not particularly limited, but is preferably a gas atmosphere in which 0.05% to 3%, particularly 0.2%, of O2 gas is added to an inert gas (e.g., Ar gas, Kr gas, Xe gas, Ne gas). When sputtering is performed in an atmosphere in which O2 gas is not sufficiently added, the CV value of Fe / (Fe+Co) tends to decrease, and the resistivity relative to Bs tends to decrease.

[0094] The nanogranular magnetic film formed by sputtering may be subjected to annealing. The annealing temperature is not particularly limited and may be about 200° C. to 500° C., or 250° C. to 450° C. The annealing time is not particularly limited and may be about 0.1 minute to 180 minutes.

[0095] The magnetic properties of the obtained nanogranular magnetic film may be measured by any method, for example, by using VSM.

[0096] An embodiment of the present invention has been described above, but the present invention is not limited to the above embodiment. For example, in the above manufacturing method, the sputtering device is fixed and the substrate is rotated, but the sputtering device may be rotated and the substrate may be fixed. In addition, as long as it is a manufacturing method that can form a multilayer film of a nanogranular magnetic film, it may be a manufacturing method other than the method of rotating one of the substrate and the sputtering device.

[0097] The use of the nano-granular magnetic film of the present embodiment is not particularly limited. The magnetic body containing the nano-granular magnetic film is particularly suitable for use in electronic components that are used at high frequencies and require high Bs and resistivity. For example, capacitors, thin film inductors, noise filters, separators, magneto-optical elements, TMR heads, GMR heads, magnetic sensors, magnetic recording media, etc. can be cited.

[0098] Example

[0099] Hereinafter, the present invention will be specifically described based on examples.

[0100] (Experimental Example 1)

[0101] use Figure 2 to Figure 4 The device shown forms a nanogranular magnetic film on a substrate. L1 = 90 mm, L2 = 2 inches, L3 = 3 inches, L4 = 2 inches, and L5 = 4 inches. A silicon substrate with a thermal oxide film having a thickness of 0.28 mm is used as the substrate. In addition, as a pretreatment of the substrate, a surface treatment using a UV / O3 method is performed for 20 minutes. Furthermore, reverse sputtering is performed for 5 minutes under Ar gas, pressure 1 Pa, and RF 100 W.

[0102] A sputtering target having a composition capable of obtaining a magnetic film having a composition shown in each table and having a thickness of 2 mm was prepared.

[0103] Then, use Figure 2 to Figure 4 The apparatus shown forms a nanogranular magnetic film by sputtering. The presence or absence of pretreatment (UV / O3, reverse sputtering), the rotation speed of the rotating plate during sputtering, the continuous film formation time, the continuous film formation thickness, the presence or absence of O2 in the Ar gas, and whether the target material is a mixed sintering target are shown in Table 1. SPF430H manufactured by ANELVACorporation was used as the sputtering apparatus.

[0104] By performing simple quantitative analysis using EDX (manufactured by JEOL Ltd.), it was confirmed that the composition of the first phase and the composition of the second phase in the obtained nanogranular magnetic film were the compositions shown in Table 1.

[0105] It was confirmed by using XRF (Primus4 manufactured by Rigaku Corporation) that V1 / (V1+V2) in the obtained nanogranular magnetic film was the value shown in Table 1.

[0106] It was confirmed using TEM (JEM2100F manufactured by JEOL Ltd.) that the nanogranular magnetic film of each sample had a structure in which minute domains of the first phase were dispersed in the second phase.

[0107] The method for measuring the CV value of Fe / (Fe+Co) is described below. First, in the obtained nanogranular magnetic film, a rectangular parallelepiped with a side length of 40nm×40nm×50nm is set as the measurement range, and 80,000 grids of 1nm×1nm×1nm are set continuously within the measurement range. Then, the Fe content and Co content in each grid are measured by a three-dimensional atom probe (3DAP), and Fe / (Fe+Co) of each grid is calculated as the atomic ratio.

[0108] Then, the standard deviation and average value of Fe / (Fe+Co) of each mesh were calculated, and the CV value was calculated by dividing the standard deviation by the average value. The average value of Fe / (Fe+Co) of each mesh substantially coincides with the Fe / (Fe+Co) of the entire nanogranular magnetic film.

[0109] The saturation magnetic flux density Bs was measured using VSM (TM-VSM331483-HGC) manufactured by Tamagawa Seisakusho Co., Ltd.

[0110] The sheet resistance was measured using a resistivity meter (Loresta-EP MCP-T360 manufactured by Mitsubishi Chemical), and the measured resistivity was calculated from the sheet resistance.

[0111] The following is a method for measuring the reference resistivity for calculating the performance index.

[0112] First, a nanogranular magnetic film was produced under substantially the same conditions using a conventional sputtering method without rotation, except that the Fe:Co ratio in the first phase was different from each other. In other words, the nanogranular magnetic film was produced under substantially the same conditions, except that the Fe:Co ratio in the first phase was approximately 85:15, 70:30, 45:55, and 15:85 in terms of atomic ratio.

[0113] As for the specific manufacturing conditions, the rotation speed was set to 0, the continuous film forming time was set to 25000 seconds, the process gas during sputtering was a mixed gas of 0.2% O2 in Ar, and the continuous film forming thickness was set to be within the range of (5000±200)nm. In addition, nanogranular magnetic films with the same composition were prepared except that the Fe:Co in the first phase was different. In addition, nanogranular magnetic films of Comparative Examples 1 to 4 were prepared in Experimental Example 1.

[0114] Next, the saturation magnetic flux density Bs and the measured resistivity of the nanogranular magnetic films of Comparative Examples 1 to 4 were measured by the above-mentioned method.

[0115] Next, the points of Comparative Examples 2 to 4 are plotted on an xy plane with Bs (T) on the x-axis and resistivity (Ωcm) on the y-axis. Then, the formula of the performance curve is derived by power approximation. In addition, the formula of the performance curve derived from Comparative Examples 2 to 4 is y = 0.0044 × x -11.25 .

[0116] The resistivity obtained by substituting the Bs value of each nanogranular magnetic film into the formula of the derived performance curve is set as the reference resistivity. Then, the value obtained by dividing the measured resistivity of each nanogranular magnetic film by the reference resistivity is set as the performance index. When the performance index is 1.20 or more, it is set as good.

[0117] In Comparative Example 5, the process was carried out under the same conditions as in Example 3 except that Ar was used as the process gas during sputtering. In Comparative Example 6, the composition of the first phase, the composition of the second phase, and V1 / (V1+V2) of the nanogranular magnetic film finally obtained were the same as those in Example 3, and a 5 mm×5 mm Fe chip and a Co chip were arranged on a commercially available SiO2 target.

[0118] In Comparative Example 7, the same conditions as those of Example 3 were used except that the UV / O3 treatment and the reverse sputtering were not performed.

[0119] [Table 1]

[0120]

[0121] According to Table 1, in Examples 1 to 4 in which the rotating plate was rotated at a rotation speed of 12 rpm, the CV value was within the prescribed range. In addition, in Examples 1 to 4, the performance index was good. That is, the resistivity relative to Bs was higher and better than that of the conventional nanogranular magnetic film formed without rotation.

[0122] In Comparative Examples 5 and 6 in which other production conditions were changed, the CV values ​​were both lower than 0.150, and the performance index was less than 1.20.

[0123] In Comparative Example 7 in which no pretreatment was performed, the film peeled off from the substrate and could not be evaluated.

[0124] (Experimental Example 2)

[0125] In Comparative Examples 8 to 10 and Examples 5 to 8, the same conditions as in Example 2 were used except that the rotation speed was changed between 1 rpm and 40 rpm. Similarly, in Comparative Examples 11 to 12 and Examples 9 to 11, the same conditions as in Example 3 were used except that the rotation speed was changed between 2 rpm and 40 rpm. In Comparative Examples 13 to 14 and Examples 12 to 14, the same conditions as in Example 4 were used except that the rotation speed was changed between 2 rpm and 40 rpm. The results are shown in Table 2.

[0126] [Table 2]

[0127]

[0128] According to Table 2, Examples 5 to 14 having CV values ​​within the prescribed range have good performance indexes like Examples 2 to 4. In contrast, Comparative Examples 8 to 14 having CV values ​​outside the prescribed range all have poor performance indexes.

[0129] (Experimental Example 3)

[0130] In Comparative Examples 15 to 26 and Examples 15 to 26 shown in Table 3, the same conditions as Comparative Examples 2 to 4 and Examples 2 to 4 were used except that an additive element chip composed of an additive element was provided on the sputtering target. Each additive element chip was formed into a rectangular parallelepiped shape with two largest faces being 5 mm square and a thickness of about 0.5 mm. The number of additive element chips was set so that the composition of the first phase and the composition of the second phase of the nanogranular magnetic film finally obtained were the compositions shown in the tables, and V1 / (V1+V2) was a value close to that of Experimental Example 1. The composition of each phase of the nanogranular magnetic film shown in the tables was set to the composition when it was assumed that all the additive elements were contained in the first phase. In Experimental Examples 3 to 4 and 6 to 8, it was actually confirmed that substantially all the additive elements were contained in the first phase.

[0131] First, the performance curve formula was derived from the comparative examples in which the types and amounts of added elements were the same and only the ratios of Fe and Co were different. The performance curve formula derived from the comparative examples 15 to 17 in which 1 atomic % of Nb was added was y=0.0033×x -11.11 The formula of the performance curve derived from Comparative Examples 18 to 20 in which 2 atomic % of Nb was added is y=0.0020×x -11.18 The formula of the performance curve derived from Comparative Examples 21 to 23 in which 5 atomic % of Nb was added is y=0.0008×x -11.16 Furthermore, the formula of the performance curve derived from Comparative Examples 24 to 26 in which 10 atomic % of Nb was added is y=0.0004×x -11.3 .

[0132] The performance curves derived from Comparative Examples 27 to 29 in which 2 atomic % of Mo was added are given by the formula y=0.0016×x -11.37 The formula of the performance curve derived from Comparative Examples 30 to 32 in which 2 atomic % of Cu was added is y=0.0022×x -11.05 .

[0133] The resistivity obtained by substituting the Bs value of each nanogranular magnetic film into the formula of the performance curve derived from the comparative example with the same type and amount of added elements was set as the reference resistivity. Then, the value obtained by dividing the measured resistivity of each nanogranular magnetic film by the reference resistivity was set as the performance index. The results are shown in Tables 3 and 4.

[0134] [Table 3]

[0135]

[0136] [Table 4]

[0137]

[0138] According to Tables 3 and 4, the CV values ​​of the examples in which the rotating plate was rotated at 12 rpm were within the specified range and the performance index was good. That is, the resistivity relative to Bs was higher and better than that of the conventional nanogranular magnetic film formed without rotation.

[0139] (Experimental Example 4)

[0140] In Experimental Examples 1 to 3, three comparative examples were prepared according to the type and amount of the added element, and the formula of the performance curve was derived. In Experimental Example 4, a method of tentatively confirming the characteristics of the nanogranular magnetic film by a simple method was studied.

[0141] The performance curve formula is derived by exponential approximation. Therefore, from the general formula y = A × x B express.

[0142] When the performance curves derived in Experimental Examples 1 to 3 are compared, the change in the value of A caused by the change in the content of the added element is large, and the change in the value of B is small. On the other hand, if the content of the added element is the same, the change in the value of A is small, and the change in the value of B is also small even if the type of the added element is changed.

[0143] Therefore, even when the type of the added element is different, it is considered that sufficiently accurate evaluation can be performed as long as the performance index is calculated by assuming that the type of the added element is Nb.

[0144] For the performance curves A and B derived from Comparative Examples 2 to 4 and 15 to 26, when there is no additive element (0% additive element), A = 0.0044, B = -11.25, when the additive element is 1%, A = 0.0033, B = -11.11, when the additive element is 2%, A = 0.0020, B = -11.18, when the additive element is 5%, A = 0.0008, B = -11.16, and when the additive element is 10%, A = 0.0004, B = -11.30. Therefore, A needs to select a value according to the concentration of the additive element, and B has nothing to do with the concentration of the additive element, and a fixed value can be used.

[0145] Next, the details of the method of selecting A and B in the method of temporarily confirming the characteristics of the nanogranular magnetic film by a simple method will be described.

[0146] (Selection method of A)

[0147] Create a graph with the amount of added element added (%) on the horizontal axis and the value of A on the vertical axis. Then, plot point a (0, 0.0044), point b (1, 0.0033), point c (2, 0.0020), point d (5, 0.0008), and point e (10, 0.0004) on the graph. Furthermore, connect point a and point b with a straight line, connect point b and point c with a straight line, connect point c and point d with a straight line, and connect point d and point e with a straight line. Using the resulting line graph, select A according to the amount of added element added.

[0148] For example, when the amount of the additive element added is 0.6%, the selected A is 0.0044×0.4+0.0033×0.6=0.00374.

[0149] (Selection method of B)

[0150] Regardless of the concentration of the added element, -11.20 is selected for B. The value of B is the value of B at each of the above-mentioned addition amounts, that is, the value obtained by arithmetic average of -11.25, -11.11, -11.18, -11.16 and -11.30.

[0151] (Definition of Simple Performance Index)

[0152] Relative to the general formula y = A × x B The calculation formula obtained by substituting the addition amount into A and B selected by the above selection method is defined as the formula of the simple performance curve, the reference resistivity obtained by the formula is defined as the simple reference resistivity, and the performance index obtained by the simple reference resistivity and the measured value of the resistivity is defined as the simple performance index. By using the formula of the simple performance curve, it is possible to calculate the simple performance index and evaluate the characteristics without manufacturing a sample with a rotation speed of 0 rpm.

[0153] Except for changing the rotation speed, the performance index and the simplified performance index were compared for Comparative Examples 11 to 12 and Examples 3, 9 to 11, which were substantially the same conditions. Since the added elements in these samples were 0%, the parameters of the formula of the simplified performance curve were A = 0.0044, B = -11.20. The calculation results of the simplified performance index are shown in Table 5 together with the performance index.

[0154] The performance index and the simplified performance index were compared for Examples 18 to 20, 27 to 29, and 30 to 32, in which the amount of the added element was 2% and the types of the added element were different. Since the amount of the added element was 2%, the parameters of the formula of the simplified performance curve were A = 0.0020 and B = -11.20. The calculation results of the simplified performance index are shown in Table 6 together with the performance index.

[0155] [Table 5]

[0156]

[0157] [Table 6]

[0158]

[0159] In all the comparative examples and examples described in Tables 5 and 6, the performance index and the simplified performance index are different, but are relatively close values. Therefore, even when the simplified performance index is used, sufficiently accurate evaluation can be performed.

[0160] (Experimental Example 5)

[0161] In Examples 33 to 44, except that the type of the added element was changed from that of Examples 19, 28, and 31, the same conditions were used, in Examples 45 to 46, except that the type of the added element was changed from that of Example 22, the same conditions were used, and in Examples 47 to 48, except that the type of the added element was changed from that of Example 25, the same conditions were used, and the CV value and the simple performance index were obtained. The results are shown in Table 7.

[0162] [Table 7]

[0163]

[0164] According to Table 7, even when the type of added element is changed, the CV value of the obtained nanogranular magnetic film is 0.150 or more and 0.500 or less, and the simple performance index is good. Even when three comparative examples are prepared for the composition of each embodiment and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.

[0165] (Experimental Example 6)

[0166] The changes in the CV value and the simple performance index when the rotation speed during the production of the nanogranular magnetic film to which the additive element is added is changed were confirmed. In Comparative Examples 33 to 34 and Examples 49 to 50, the same conditions as in Example 31 were used except that the rotation speed was changed. In Comparative Examples 35 to 36 and Examples 51 to 52, the same conditions as in Example 39 were used except that the rotation speed was changed. In Comparative Examples 37 to 38 and Examples 53 to 54, the same conditions as in Example 44 were used except that the rotation speed was changed. The results are shown in Table 8.

[0167] [Table 8]

[0168]

[0169] According to Table 8, in Examples 31, 39, 44, and 49 to 54, the CV values ​​were 0.150 or more and 0.500 or less, and the simple performance index was good. That is, no difference due to the type of added element was confirmed.

[0170] (Experimental Example 7)

[0171] The same conditions as in Example 3 were used except that the compound contained in the second phase was changed from SiO2. In Examples 62 to 64, the volume ratio of SiO2 and Al2O3 in the second phase was changed. In Experimental Example 7, even when the type of compound contained in the second phase was different, the compound was regarded as equivalent to SiO2 and the simplified performance index was calculated. The results are shown in Table 9.

[0172] [Table 9]

[0173]

[0174] Table 9 shows that even when the compound contained in the second phase is changed, the CV value and simple performance index of the obtained nanogranular magnetic film are good. Even when three comparative examples are prepared for the composition of each example and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.

[0175] (Experimental Example 8-1)

[0176] The experiment was conducted under the same conditions as in Example 3 except that V1 / (V1+V2) was greatly changed. In Experimental Example 8-1, even when V1 / (V1+V2) was greatly different, V1 / (V1+V2) was considered to be about 46% and the simple performance index was calculated. The results are shown in Table 10-1.

[0177] [Table 10-1]

[0178]

[0179] According to Table 10-1, even if V1 / (V1+V2) is greatly changed, the CV value and simple performance index of the obtained nanogranular magnetic film are good. Even if three comparative examples are prepared for each example and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.

[0180] (Experimental Example 8-2)

[0181] In Examples 66, 67, 102, and 103, the ratio of Fe and Co in the first phase was changed and implemented. The results are shown in Table 10-2.

[0182] Furthermore, Examples 103 and 108 to 110 were carried out by changing the compound contained in the second phase. The results are shown in Table 10-2.

[0183] [Table 10-2]

[0184]

[0185] According to Table 10-2, even if the composition of the first phase and / or the compound contained in the second phase is changed, the CV value and simple performance index of the obtained nanogranular magnetic film are good. Even if three comparative examples are prepared for each embodiment and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.

[0186] (Experimental Example 8-3)

[0187] For Examples 67, 102, 103, 108 to 110, and 117 to 120, the same process was performed except that nitrogen was introduced into the second phase. In order to introduce nitrogen into the second phase, nitrogen was introduced into the process gas during sputtering together with 0.2% oxygen. The ratio of nitrogen in the second phase to the total amount of oxygen and nitrogen (N / (N+O)) was changed by changing the nitrogen concentration in the process gas. The results are shown in Table 10-3.

[0188] In Examples 121 to 124, Ar gas into which 1% nitrogen was introduced was used as the process gas. In Examples 125 to 128, Ar gas into which 2% nitrogen was introduced was used as the process gas. In Examples 129 to 132 and 139 to 142, Ar gas into which 4% nitrogen was introduced was used as the process gas. In Examples 133 to 138, Ar gas into which 6% nitrogen was introduced was used as the process gas. In all Examples, the total flow rate of the process gas was 20 sccm in terms of Ar and nitrogen.

[0189] The method for measuring N / (N+O) is described below. When sputtering a nanogranular magnetic film, a 20 mm × 20 mm × 50 μm Ni foil is prepared together with a silicon substrate with a thermal oxide film. The length in the thickness direction is 50 μm. In addition, the N / (N+O) of the nanogranular magnetic film formed on the Ni foil is measured by a pulse heating melt extraction method using TC600 manufactured by LECO.

[0190] [Table 10-3]

[0191]

[0192] According to Table 10-3, even if the composition of the first phase and / or the compound contained in the second phase is changed, the CV value and simple performance index of the obtained nanogranular magnetic film are good. Even if three comparative examples are prepared for each embodiment and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.

[0193] (Experimental Example 8-4)

[0194] Examples 143 to 158 were carried out in the same manner as Examples 121 to 124, except that an additive element chip composed of an additive element was provided on the sputtering target in the same manner as in Experimental Example 3. Furthermore, Examples 159 to 162 were carried out in the same manner as Examples 155 to 158, except that the nitrogen concentration of the process gas was changed to 6%. The results are shown in Table 10-4.

[0195] [Table 10-4]

[0196]

[0197] According to Table 10-4, even if the composition of the first phase and / or the compound contained in the second phase is changed, the CV value and simple performance index of the obtained nanogranular magnetic film are good. Even if three comparative examples are prepared for each embodiment and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.

[0198] (Experimental Example 8-5)

[0199] For Examples 155 to 158, the ratio of Fe and Co in the first phase was changed to implement Examples 163 to 170. For Examples 155 to 158, the number of additive element chips was changed to implement Examples 171 to 174. Furthermore, for Example 156, the type of additive element was changed to implement Examples 175 to 184. The results are shown in Table 10-5.

[0200] [Table 10-5]

[0201]

[0202] According to Table 10-5, even if the composition of the first phase is changed, the CV value and simple performance index of the obtained nanogranular magnetic film are good. Even if three comparative examples are prepared for V1 / (V1+V2) of each embodiment and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.

[0203] (Experimental Example 9)

[0204] Except for the fact that the film thickness was greatly changed, the experiment was carried out under the same conditions as in Example 3, Example 103, and Example 134. In Experimental Example 9, even when the film thickness was greatly different, the film thickness was considered to be about 5000 nm and the simple performance index was calculated. The results are shown in Table 11.

[0205] [Table 11]

[0206]

[0207] Table 11 shows that the CV value and simple performance index of the obtained nanogranular magnetic film are good even if the film thickness is greatly changed. Even if three comparative examples are prepared for the film thickness of each example and the performance index is calculated, the calculated performance index is likely to be 1.20 or more.

[0208] According to the above-mentioned embodiments, the less the amount of the additive element is, the easier it is to absolutely improve both Bs and resistivity. From the viewpoint of absolutely improving both Bs and resistivity, the performance curve formula derived from Comparative Examples 2 to 4 without the additive element, y=0.0044×x -11.25 The calculated performance index is more preferably 1.20 or more.

Claims

1. A nanoparticle magnetic film, wherein: The nanogranular magnetic film has a structure in which micro-regions of a first phase are dispersed in a second phase. The first phase contains Fe and Co, and the second phase contains one or more selected from O, N and F. A measurement range is set for the nanogranular magnetic film, the measurement range is divided into 80,000 or more 1 nm×1 nm×1 nm grids, and Fe / (Fe+Co) of each grid is measured as an atomic ratio. In this case, The CV value of Fe / (Fe+Co) calculated for each mesh is 0.150 or more and 0.500 or less.

2. The nanogranular magnetic film according to claim 1, wherein A volume ratio of the first phase to a total volume of the first phase and the second phase is 40% to 65%.

3. The nanogranular magnetic film according to claim 1 or 2, wherein: The average value of Fe / (Fe+Co) calculated for each mesh is 0.15 or more and 0.85 or less.

4. An electronic component, wherein: A nanogranular magnetic film according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Amorphous alloy containing nitrogen

    JP1985152651A

  • Soft magnetic alloy and magnetic component

    WO2023127199A1